Sala de aula invertida e os processos motivacionais de estudantes nas aulas de apoio de língua inglesa - Barros, Livia Cruz Pinheiro de (2019)
The English language is increasingly close to our students, whether for the interest in leisure activities such as series, music, games, travel, or even for the desire to be more fluent in the performance of a qualifying exam for college or scholarship to study abroad. But the truth is that not everyone gets early quality access to the language, thus generating some limitations when faced with the study of this in elementary school (6th to 9th grade). Thinking about how to overcome the difficulties that some students bring in the acquisition of a new language, this research aims to verify the contributions of the flipped classroom in the English Language reinforcement classes of the elementary school, as a motivating factor to the students who has lack of knowledge in English Language. It will be considered a glance on the Military School of Porto Alegre, one of the thirteen schools of the Military School System of Brazil (SCMB). The aim is to investigate the implications of increasing the use of active methodologies, especially the flipped classroom, to reinforcement classes in subjects where the deficiency of curricular prerequisites is identified, the reference in this work is the discipline of English language. This study is based on the desire to take better advantage of the time allocated to reinforcement classes in order to develop the protagonism of the student, and from this, to be able to devise strategies to combat poor achievement in regular classes, so the study pervades the foundations of the processes of teaching and learning to reflect on how the flipped classroom can effectively contribute to the consolidation of knowledge by the student and also how the study of motivational processes operate to better apply the resources used in this methodology to work the autonomy of the student. As theoretical reference, the authors considered are Paulo Freire, Jerome Bruner, Jonathan Bergmann, Aron Sams, Lilian Bacich, José Moran, Fausto Camargo, Thuinie Daros, Evely Boruchovitch and Bettina Steren dos Santos. The methodological design to be adopted is the qualitative type with an exploratory feature, with emphasis on action research, and it will be done through observation, questionnaire and a collective interview applied to the group of students at the end of the activities. For the analysis, the assumptions of Roque Moraes and Maria do Carmo Galiazzi will be adopted to carry out the discursive textual analysis. The state of knowledge contributed with the object of research in the perception of the absence of studies related to the use of the flipped classroom in the intended field, showing then the relevance of this research.